Pendidikan Kesehatan Cuci Tangan Pakai Sabun dengan Media Video, Terbukti Efektif dalam Meningkatkan Kesiapsiagaan Keluarga di Masa Pandemi COVID-19 - Gede Dalem Gilang Mahajaya Putra; Ketut Sudiantara; I Ketut Gama; I Wayan Mustika (FORIKES, 2023)
The COVID-19 pandemic is a disease outbreak that has had a negative impact on all levels of society, especially families, so it requires preparedness. This research provides health education on washing hands with soap using video media. The research design is one group pretest-posttest. The sample size is 138 people selected by stratified random sampling technique. Data was collected through observation, then analyzed using the Wilcoxon test. Before the health education was carried out using video media, the respondents' preparedness was in the unprepared category, while after the health education was given it increased to the ready category. Statistical analysis showed a value of p = 0.000, so there was a difference in readiness between before and after carrying out health education on washing hands with soap using video media. It was concluded that health education on washing hands with soap using video media is effective in increasing family preparedness during the COVID-19 pandemic.Keywords: Covid -19; preparedness; washing hands ABSTRAK Pandemi COVID-19 merupakan wabah penyakit yang sudah memberikan dampak buruk terhadap semua kalangan masyarakat terutama keluarga, sehingga memerlukan kesiapsiagaan. Penelitian ini memberikan pendidikan kesehatan cuci tangan pakai sabun dengan media video. Rancangan penelitian ini adalah one group pretest-posttest. Besar sampel adalah 138 orang yang dipilih dengan teknik stratified random sampling. Data dikumpulkan melalui observasi, lalu dilakukan analisis menggunakan uji Wilcoxon. Sebelum dilakukan pendidikan kesehatan dengan media video, kesiapsiagaan responden berada pada kategori kurang siap, sedangkan setelah diperikan pendidikan kesehatan meningkat ke dalam kategori siap. Analisis statistik menunjukkan nilai p = 0,000, maka ada perbedaan kesiapan antara sebelum dan sesudah dilalukan pendidikan kesehatan cuci tangan pakai sabun dengan media video. Disimpulkan bahwa pendidikan kesehatan cuci tangan pakai sabun dengan media video efektif untuk meningkatkan kesiapsiagaan keluarga di masa pandemi COVID-19.Kata kunci: Covid -19; kesiapsiagaan; cuci tangan